The Influence of Financial Literacy and Investment Knowledge on Mutual Fund Investment Interest Among Generation Z with Investment Motivation as a Mediating Variable - Risna Widianti; Euis Ajizah; Wahyu Hari Prihantono (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of financia l literacy and investment knowledge on mutual fund investment interest among Generation Z, with investment motivation as a mediating variable. The research employs a quantitative approach using a survey method by distributing questionnaires to 100 Generation Z respondents who are mutual fund investors. The sampling technique used is probability sampling with a simple random sampling method. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through the SmartPLS application. The results indicate that financial literacy does not have a significant effect on investment interest, but it has a positive and significant effect on investment motivation. Furthermore, investment motivation is proven to have a positive and significant effect on investment interest. Investment knowledge also shows a positive and significant influence on both investment interest and investment motivation. These findings suggest that investment knowledge and investment motivation are important factors in increasing mutual fund investment interest among Generation Z. Therefore, improving investment education and financial literacy is essential to encourage more rational and sustainable investment participation among young people.